A validated LCâMS/MS method for the determination of tolterodine and its metabolite in rat plasma and application to pharmacokinetic study - Rihana Parveen Shaik; Srinivasa Babu Puttagunta; Chandrasekhar Bannoth Kothapalli; Bahlul Zayed Sh. Awen; B.R. Challa (Elsevier, 2013)
Liquid chromatographyâtandem mass spectrometry (LCâMS/MS) method was used for simultaneous quantification of tolterodine and its metabolite 5-hydroxy methyl tolterodine in rat plasma. Tolterodine-d6 and 5-hydroxy methyl tolterodine-d14 were used as internal standards (IS). Chromatographic separation was performed on Ascentis Express RP amide (50Â mmÃ4.6Â mm, 2.7Â Î¼m) column with an isocratic mobile phase composed of 10Â mM ammonium acetate and acetonitrile in the ratio of 20:80 (v/v), at a flow-rate of 0.5Â mL/min. Tolterodine, tolterodine-d6, 5-hydroxy methyl tolterodine and 5-hydroxy methyl tolterodine-d14 were detected with proton adducts at m/z 326.1â147.1, 332.3â153.1, 342.2â223.1 and 356.2â223.1 in multiple reaction monitoring (MRM) positive mode respectively. The drug, metabolite and internal standards were extracted by liquidâliquid extraction method. The method was validated over a linear concentration range of 20.00â5000.00Â pg/mL for tolterodine and 20.00â5000.00Â pg/mL for 5-hydroxy methyl tolterodine. This method demonstrated intra- and inter-day precision of 0.62â6.36% and 1.73â4.84% for tolterodine, 1.38â4.22% and 1.62â4.25% for 5-hydroxy methyl tolterodine respectively. This method also demonstrated intra- and inter-day accuracy of 98.75â103.56% and 99.20â104.40% for tolterodine, 98.08â104.67% and 98.73â103.06% for 5-hydroxy methyl tolterodine respectively. Both analytes were found to be stable throughout freezeâthaw cycles, bench top and postoperative stability studies. This method was successfully applied for the pharmacokinetic analysis of rat plasma samples following i.v. administration. Keywords: LCâMS/MS, Tolterodine, 5-Hydroxy methyl tolterodine, Pharmacokinetics